Prevalence, pathogenesis, and treatment options for mastocytosis-related osteoporosis. Issue 8 (August 2016) - Rossini, M.; Zanotti, R.; Orsolini, G.; Tripi, G.; Viapiana, O.; Idolazzi, L.; Zamò, A.; Bonadonna, P.; Kunnathully, V.; Adami, S.; Gatti, D.
Abstract Mastocytosis is a rare condition characterized by abnormal mast cell proliferation and a broad spectrum of manifestations, including various organs and tissues. Osteoporosis is one of the most frequent manifestations of systemic mastocytosis, particularly in adults. Osteoporosis secondary to systemic mastocytosis is a cause of unexplained low bone mineral density that should be investigated when accompanied by suspicious clinical elements. Bone involvement is often complicated by a high recurrence of fragility fractures, mainly vertebral, leading to severe disability. The mechanism of bone loss is the result of different pathways, not yet fully discovered. The main actor is the osteoclast with a relative or absolute predominance of bone resorption. Among the stimuli that drive osteoclast activity, the most important one seems to be the RANK-RANKL signaling, but also histamine and other cytokines play a significant role in the process. The central role of osteoclasts made bisphosphonates, as anti-resorptive drugs, the most rational treatment for bone involvement in systemic mastocytosis. There are a few small studies supporting this approach, with large heterogeneity of drug and administration scheme. Currently, zoledronate has the best evidence in terms of gain in bone mineral density and bone turnover suppression, two surrogate markers of anti-fracture efficacy.